What drives farmers to use conservation agriculture? Application of mediated protection motivation theory - Bazrafkan, Khadijeh; Valizadeh, Naser; Khannejad, Setareh; Kianmehr, Nazanin; Bijani, Masoud; Hayati, Dariush (Frontiers in Psychology, 2022)
Conservation agriculture is an approach for managing agricultural ecosystems, improving productivity, increasing benefits and food security, and preserving resources and the environment. The core purpose of this study was to analyze the constructs affecting the intention to use conservation agriculture measures. For this purpose, protection motivation theory was applied as the theoretical framework. Validation of the model was done using a cross-sectional survey among Iranian farmers, and SMART PLS software was used to test the hypotheses. The results showed that the direct effects of the five constructs of perceived severity, perceived vulnerability, response cost, response efficacy, and self-efficacy were significant on the intention to use conservation agriculture measures. In addition, the variables of perceived severity, response cost, and perceived self-efficacy had significant effects on the fear of not using conservation agriculture measures. The results of the bootstrapping analysis indicated that the fear of not using conservation agriculture measures significantly mediated the effects of perceived severity, response cost, and self-efficacy on the intention to use conservation agriculture. The results of the present research help to develop protection motivation theory by defining new relationships between its variables and achieving a deeper understanding of these relationships. The results also can pave the way for social and psychological interventions in the field of adopting the principles of conservation agriculture in agricultural societies. Finally, the results of this research can be used as a decision-making tool and help for users and planners of behavioral changes to better identify the focus points and necessary strategies.